Yield and Mineral Content of Scaly-Bark-Affected Sweet Orange Trees - Guardiola, J. L.; González-Sicilia, Eusebio; Marti-Fabregat, Francisco (IOCV, 2023)
The development of psorosis bark lesions reduces the yield of sweet orange trees in comparison with that of infected trees without conspicuous trunk symptoms. Salibe and Moreira (8) quoted other authors to the effect that successive stages of psorosis reduce yields from 0.5 per cent to 72 per cent in comparison with control plants; the control plants may or may not have been infected.